Method for producing electrode mixture, electrode mixture, electrode and lithium ion battery

By dropping the slurry of the active substance and the coating liquid and drying it in the heating gas, active substance particles of the coating layer are obtained, and the problem of increasing the resistance of the electrode and battery is solved, and the process is increased and the resistance is reduced.

CN115939333BActive Publication Date: 2025-04-15TOYOTA JIDOSHA KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211131291.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-22
Filing Date
2022-09-15
Publication Date
2025-04-15
Estimated Expiration
2042-09-15

AI Technical Summary

Technical Problem

The prior art is difficult to take into account both the granulation inhibition of active substances and the rapidity of the manufacturing process, resulting in an increase in the resistance of the electrode and the battery.

Method used

By dropping the slurry containing the active substance and the coating liquid, and drying the gas stream in the heating gas, the first precursor and the second precursor are obtained, and then sintered to obtain the first and second particles. The first particle has an active material and a coating layer, and the second particle does not contain an active material but contains the same components as the coating layer.

Benefits of technology

The inhibition of active material granulation and the rapidity of the manufacturing process are achieved, and electrodes and batteries with low resistance are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115939333B_ABST
    Figure CN115939333B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing an electrode mixture, an electrode mixture, an electrode and a lithium ion battery. When manufacturing an electrode mixture containing a coated active material, both the suppression of granulation of the active material and the speeding up of the manufacturing process are taken into account. The method for manufacturing an electrode mixture comprises: dropletizing a slurry containing an active material and a coating liquid to obtain slurry droplets; airflow drying the slurry droplets in a heated gas to obtain a first precursor and a second precursor; and calcining the first precursor and the second precursor to obtain a first particle and a second particle, wherein the first precursor contains an active material and a component from the coating liquid, the second precursor does not contain an active material but contains a component from the coating liquid, the first particle has an active material and a coating layer covering at least a portion of the surface of the active material, and the second particle does not contain an active material but contains a component identical to the component constituting the coating layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application discloses a method for manufacturing an electrode mixture, an electrode mixture, an electrode and a lithium ion battery. Background Art

[0002] Patent Document 1 discloses a method of producing an active material composite (coated active material) by spraying a specific coating liquid onto the surface of an active material using a tumbling flow coating device, drying the coating liquid, and then calcining the coating liquid.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 6269645 Summary of the invention

[0006] Problems to be solved by the invention

[0007] In the method disclosed in Patent Document 1, when the coating liquid is sprayed on the active material at a high speed, granulation of the active material is likely to occur. When the granulated active material is used to form an electrode or a battery, for example, the resistance of the electrode or the battery may increase. On the other hand, when the coating liquid is sprayed at a low speed in order to suppress the granulation of the active material, the time required to manufacture the coated active material becomes longer. In this way, in the prior art, it is difficult to take into account both the suppression of the granulation of the active material and the speeding up of the manufacturing process.

[0008] Means for solving problems

[0009] As one of the means for solving the above-mentioned problems, the present application discloses a method for manufacturing an electrode mixture, which comprises:

[0010] Dropping a slurry containing an active substance and a coating liquid to obtain slurry droplets;

[0011] Allowing the slurry droplets to be air-dried in a heated gas to obtain a first precursor and a second precursor; and

[0012] The first precursor and the second precursor are fired to obtain first particles and second particles, wherein:

[0013] The first precursor comprises the active material and a component from the coating liquid,

[0014] The second precursor does not contain the active substance and contains components from the coating liquid.

[0015] The first particle has the active material and a coating layer that covers at least a portion of the surface of the active material.

[0016] The second particles do not contain the active material, and contain the same components as those constituting the coating layer.

[0017] In the method of the present disclosure, the temperature of the heating gas may be above 250°C.

[0018] In the method of the present disclosure, the slurry droplets may be obtained by spraying the slurry.

[0019] In the method of the present disclosure, the coating solution may include at least a lithium source and a niobium source.

[0020] In the method of the present disclosure, the coating solution may contain a peroxo complex of niobium as the niobium source.

[0021] The method of the present disclosure may include mixing at least the first particles, the second particles, and a solid electrolyte.

[0022] As one of the means for solving the above-mentioned problems, the present application discloses an electrode mixture, which comprises at least a first particle and a second particle, wherein the first particle has an active substance and a coating layer covering at least a portion of the surface of the active substance, and the second particle does not contain the active substance and comprises the same components as those constituting the coating layer.

[0023] In the electrode mixture of the present disclosure, the roundness of the cross section of the second particles may be 0.30 or more and 1.00 or less.

[0024] In the electrode mixture of the present disclosure, the coating layer may contain at least lithium and niobium as constituent elements.

[0025] The electrode mixture disclosed herein may include at least the first particles, the second particles, and a solid electrolyte.

[0026] As one of means for solving the above-mentioned problems, the present application discloses an electrode including a layer containing the electrode mixture disclosed herein.

[0027] In the electrode disclosed herein, when observing a cross section of the layer, the ratio of the second particles in the layer may be 0.02 area % or more.

[0028] As one of means for solving the above-mentioned problems, the present application discloses a lithium ion battery including the electrode disclosed herein.

[0029] Effects of the Invention

[0030] According to the method disclosed herein, it is easy to achieve both suppression of granulation of active materials and speeding up the production process. By using the electrode mixture disclosed herein to construct an electrode or a battery, for example, an electrode or a battery with low resistance can be easily obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 An example of the flow of the method for producing an electrode mixture is shown.

[0032] Figure 2A An example of slurry droplets is schematically shown.

[0033] Figure 2B An example of slurry droplets is schematically shown.

[0034] Figure 2C An example of slurry droplets is schematically shown.

[0035] Figure 2D An example of slurry droplets is schematically shown.

[0036] Figure 3 An example of air flow drying is schematically shown.

[0037] Figure 4A An example of the effect of airflow drying is schematically shown.

[0038] Figure 4B An example of the effect of airflow drying is schematically shown.

[0039] Figure 5 An example of particles obtained by calcining a precursor is schematically shown.

[0040] Figure 6 An example of the configuration of an electrode is schematically shown.

[0041] Figure 7 An example of the structure of a lithium ion battery is schematically shown.

[0042] Figure 8 The flow of the production method according to the comparative example is shown.

[0043] Description of Reference Numerals

[0044] 10 Slurry droplets

[0045] 10a Active substances

[0046] 10b Coating liquid

[0047] 10c Components from coating fluid

[0048] 10d coating

[0049] 21 First Precursor

[0050] 22 Second Precursor

[0051] 31. First particle (coated with active material)

[0052] 32 The Second Particle

[0053] 50 electrodes

[0054] 50a positive electrode

[0055] 50b negative electrode

[0056] 51 electrode mixture layer

[0057] 52 Current Collector

[0058] 60 Electrolyte layer

[0059] 100 Lithium-ion battery DETAILED DESCRIPTION

[0060] 1. Method for manufacturing electrode mixture

[0061] like Figures 1 to 5 As shown in , a method S10 for manufacturing an electrode mixture according to one embodiment includes:

[0062] Step S1: forming droplets of a slurry containing an active material 10a and a coating liquid 10b to obtain slurry droplets 10;

[0063] Step S2: drying the slurry droplets 10 in a heated gas to obtain a first precursor 21 and a second precursor 22; and

[0064] Step S3 : sintering the first precursor 21 and the second precursor 22 to obtain first particles 31 and second particles 32 .

[0065] Here, the first precursor 21 contains the active material 10a and the component 10c derived from the coating liquid 10b, the second precursor 22 does not contain the active material 10a but contains the component 10c derived from the coating liquid 10b, the first particle 31 has the active material 10a and a coating layer 10d covering at least a portion of the surface of the active material 10a, and the second particle 32 does not contain the active material 10a but contains the same component as the component constituting the coating layer 10d.

[0066] 1.1 Process S1

[0067] like Figures 2A to 2D As shown, in step S1 , a slurry containing an active material 10 a and a coating liquid 10 b is formed into droplets to obtain slurry droplets 10 .

[0068] 1.1.1 Active substances

[0069] The active material may be a positive electrode active material or a negative electrode active material. Specific examples of the active material include LiCoO2, LiNi x Co1-x O2(0<x<1), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiMnO2, heterogeneous element replacement Li-Mn spinel (LiMn 1.5 Ni 0.5 O4、LiMn 1.5 Al 0.5 O4、LiMn 1.5 Mg 0.5 O4、LiMn 1.5 Co 0.5 O4、LiMn 1.5 Fe 0.5 O4、LiMn 1.5 Zn 0.5 O4, etc.), lithium titanate (such as Li4Ti5O 12 ), lithium-containing oxides such as lithium metal phosphate (LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4); various oxide-based active materials other than lithium-containing oxides; Si-based active materials such as Si and Si alloys; carbon-based active materials such as graphite and hard carbon; metallic lithium, lithium alloys, etc. Among them, substances with relatively high charge and discharge potentials can be used as positive electrode active materials, and substances with relatively low charge and discharge potentials can be used as negative electrode active materials. In particular, when the active material is a lithium-containing oxide, a higher effect can be expected from the method disclosed in the present invention. The active material can be used alone or as a mixture of two or more. The active material can be used in sulfide solid batteries.

[0070] The shape of the active material is not particularly limited as long as the dropletization of the slurry can be achieved. For example, the active material can be in particulate form. The active material particles can be solid particles or hollow particles. The active material particles can be primary particles or secondary particles formed by the aggregation of multiple primary particles. The average particle size (D50) of the active material particles can be, for example, greater than 1 nm, greater than 5 nm, or greater than 10 nm, and can be less than 500 μm, less than 100 μm, less than 50 μm, or less than 30 μm. It should be noted that the average particle size D50 is the particle size (median particle size) at the cumulative value of 50% in the volume-based particle size distribution obtained by the laser diffraction / scattering method.

[0071] 1.1.2 Coating liquid

[0072] The coating layer can be formed on the surface of the active material by using the components from the coating liquid. In addition, the second precursor and the second particle described later can be formed by using the components from the coating liquid. The coating layer can have the function of suppressing the increase of the interface resistance between the active material and other substances, for example. The type of coating liquid can be selected according to the type of active material as the coating object and the function of the target coating layer.

[0073] When a layer containing an oxide of an element A other than lithium and lithium is provided on the surface of the active material, the coating liquid may contain a lithium source and an A source. As specific examples of element A, at least one selected from B, C, Al, Si, P, S, Ti, Zr, Nb, Mo, Ta, and W can be cited. For example, when a lithium niobate layer is provided on the surface of the active material as a coating layer, the coating liquid may contain at least a lithium source and a niobium source. From the viewpoint of further improving the performance of the coating layer, the coating liquid may contain at least one of a phosphorus source and a boron source in addition to a lithium source and a niobium source. Alternatively, at least one of a phosphorus source and a boron source may be included instead of a niobium source. For example, by replacing a portion of Nb of lithium niobate with P (or doping lithium niobate with P), the voltage resistance of the coating layer can be easily improved. The coating liquid may contain lithium ions as a lithium source. For example, a coating liquid containing lithium ions as a lithium source can be obtained by dissolving a lithium compound such as LiOH, LiNO3, and Li2SO4 in a solvent. Alternatively, the coating liquid may contain a lithium alkoxide as a lithium source. In addition, the coating liquid may contain a peroxide complex of niobium as a niobium source. Alternatively, the coating liquid may contain an alkoxide of niobium as a niobium source. In particular, when the coating liquid contains a peroxide complex of niobium as a niobium source, high performance is easily obtained. There is no particular limitation on the molar ratio of the lithium source to the niobium source contained in the coating liquid. For example, the molar ratio Li / Nb may be greater than 0.5 or greater than 0.8, and may be less than 2.0 or less than 1.5. Below, (i) a coating liquid containing a peroxide complex of lithium ions and niobium, and (ii) a coating liquid containing an alkoxide of lithium and an alkoxide of niobium are exemplified.

[0074] (i) Coating liquid containing a peroxo complex of lithium ions and niobium

[0075] For example, a coating solution can be obtained by preparing a transparent solution using hydrogen peroxide, niobic acid, and ammonia water, and then adding a lithium compound to the transparent solution. 3- ) is as follows, for example.

[0076] [Chemistry 1]

[0077]

[0078] (ii) Coating solution containing lithium alkoxide and niobium alkoxide

[0079] For example, the coating liquid can be obtained by dissolving lithium ethoxide powder in a solvent and then adding a predetermined amount of niobium pentaethoxide thereto. In this case, examples of the solvent include dehydrated ethanol, dehydrated propanol, and dehydrated butanol.

[0080] The type of coating layer provided on the surface of the active material using the components from the coating liquid is not limited to a layer containing an oxide of an element A other than lithium and lithium. The method disclosed herein can be used when the surface of the active material is modified or coated with certain substances. For example, in order to increase output, prolong life, etc., the method disclosed herein can also be used when a transition metal oxide is coated on the surface of the positive and negative active materials. However, it is believed that the method disclosed herein has a particularly significant effect when a layer containing an oxide of an element A other than lithium and lithium is provided on the surface of the active material.

[0081] 1.1.3 Slurry

[0082] "Slurry" refers to a suspension or suspension containing an active substance and a coating liquid, as long as it has fluidity to the extent that it can be dropletized. In the method disclosed herein, the slurry may have fluidity to the extent that it can be dropletized using a spray nozzle or a rotary atomizer. It should be noted that the slurry may contain certain solid components and liquid components in addition to the above-mentioned active substance and coating liquid.

[0083] The solid content concentration of the slurry is determined according to the type of active material, the type of coating liquid, and the conditions of dropletization (the type of device for dropletization). There is no particular limitation on the solid content concentration in the slurry, for example, it can be more than 1 volume %, more than 5 volume %, more than 10 volume %, more than 20 volume %, more than 25 volume %, more than 30 volume %, more than 35 volume %, more than 40 volume %, more than 45 volume %, more than 50 volume %, and can be less than 70 volume %, less than 65 volume %, less than 60 volume %, less than 55 volume %, less than 50 volume %, less than 45 volume %, less than 40 volume %, less than 35 volume %, less than 30 volume %, less than 25 volume % or less than 20 volume %. From the viewpoint of more easily obtaining slurry droplets, the solid content concentration of the slurry can be more than 1 volume % or more than 5 volume %, and can be less than 40 volume %, less than 35 volume %, less than 30 volume %, less than 25 volume % or less than 20 volume %.

[0084] 1.1.4 Dropletization of slurry

[0085] The “dropletization” of the slurry refers to converting the slurry containing the active material and the coating liquid into droplets containing the active material and the coating liquid (first droplets) and droplets containing no active material but the coating liquid (second droplets).

[0086] There is no particular limitation on the method for making the slurry containing the active material and the coating liquid droplet. For example, the slurry droplets can be obtained by spraying the slurry. When spraying the slurry, a spray nozzle can be used. As a method for spraying the slurry using a spray nozzle, a pressurized nozzle method, a two-fluid nozzle method, etc. can be listed, but it is not limited to these.

[0087] When the slurry is sprayed using a spray nozzle, the nozzle diameter is not particularly limited, and the nozzle diameter may be, for example, 0.1 mm or more, 0.5 mm or more, or 1 mm or less, or 10 mm or less, 5 mm or less, or 1 mm or less.

[0088] In addition, there is no particular limitation on the spraying speed of the slurry (the supply speed (liquid delivery speed) of the slurry to the spray nozzle). The spraying speed can be adjusted according to the viscosity of the slurry, the solid content concentration, the nozzle size, etc. The spraying speed can be, for example, 0.1 g / sec or more, 0.5 g / sec or more, or 1.0 g / sec or less, or 5.0 g / sec or less, 3.5 g / sec or less, or 2.0 g / sec or less. According to the new insights of the inventors, when the spraying speed is fast, the second precursor and the second particles described later are easily generated.

[0089] As a method for dropletizing the slurry, in addition to the method of spraying the slurry using a spray nozzle as described above, for example, a method of supplying a slurry containing an active material and a coating liquid at a certain speed on a rotating disc and using centrifugal force to drop it can also be exemplified. In this case, the supply speed of the slurry can be, for example, 0.1 g / second or more, 0.5 g / second or more, or 1.0 g / second or less, 5.0 g / second or less, 3.5 g / second or less, or 2.0 g / second or less, and the supply speed can be adjusted according to the viscosity and solid content concentration of the slurry, the nozzle size, etc. Alternatively, a method of applying a high voltage to the surface of the slurry containing an active material and a coating liquid to drop it can also be adopted.

[0090] In the method of the present disclosure, for example, a spray dryer can be used to form droplets of the slurry (step S1) and to dry the slurry with airflow (step S2). The type of the spray dryer is not particularly limited, and examples thereof include a method using the above-mentioned spray nozzle and a method using a rotating disk.

[0091] 1.1.5 Slurry droplets

[0092] As described above, the "slurry droplets" may include particles (first droplets) containing an active material and a coating liquid and particles (second droplets) composed of a coating liquid. There is no particular limitation on the size of the slurry droplets. The diameter (spherical equivalent diameter) of the first droplet may be, for example, 0.1 μm or more, 0.5 μm or more, or 5.0 μm or more, or 5000 μm or less, 1000 μm or less, or 500 μm or less. The diameter (spherical equivalent diameter) of the second droplet may be, for example, 0.1 μm or more, 0.5 μm or more, or 5.0 μm or more, or 1000 μm or less, 500 μm or less, or 50 μm or less. The diameter of the slurry droplet may be measured, for example, using a two-dimensional image obtained by photographing the slurry droplet, or may be measured using a laser diffraction particle size distribution meter. Alternatively, the droplet diameter may be estimated from the operating conditions of the device that forms the slurry droplet.

[0093] In the method disclosed herein, a drop of slurry may be composed of, for example, only a coating liquid, or may include one active material particle and a coating liquid attached to the active material particle, or may include a plurality of active material particles (particle groups) and a coating liquid attached to them. An example of the morphology of a slurry drop is shown below.

[0094] like Figure 2A As shown, the slurry droplet 10 may not contain the active material 10a but may be composed of the coating liquid 10b.

[0095] like Figure 2B As shown, the slurry droplet 10 may include one active material particle 10 a and a coating liquid 10 b attached thereto, and the coating liquid 10 b may cover the entire surface of the active material particle 10 a .

[0096] like Figure 2C As shown, the slurry droplet 10 may include one active material particle 10 a and a coating liquid 10 b attached thereto, and the coating liquid 10 b may cover a portion of the surface of the active material particle 10 a.

[0097] like Figure 2D As shown, the slurry droplet 10 may include a plurality of active material particles 10a and a coating liquid 10b attached to the particles. The coating liquid 10b may cover all or part of the plurality of active material particles 10a.

[0098] 1.2 Process S2

[0099] like Figure 3 As shown, in step S2, the slurry droplets 10 obtained in step S1 are dried in a heated gas stream to obtain a first precursor 21 and a second precursor 22. The "first precursor" is a precursor of the first particles (coated active material) described later, and the "second precursor" is a precursor of the second particles described later. Figure 3As shown, the first precursor 21 contains the active material 10a and the component 10c derived from the coating liquid, and the second precursor 22 contains no active material 10a but contains the component 10c derived from the coating liquid.

[0100] 1.2.1 Airflow drying conditions

[0101] In the method disclosed herein, "airflow drying" refers to drying the slurry droplets while floating them in a high-temperature airflow. "Airflow drying" may include not only drying, but also incidental operations based on the use of dynamic airflow. By utilizing airflow drying, hot air is continuously applied to the slurry droplets or precursors, thereby continuously applying force to the slurry droplets or precursors. Using this method, step S2 may also include breaking up (crushing) the slurry droplets and precursors by airflow drying.

[0102] Specifically, when the slurry droplets are subjected to airflow drying, the following steps can be performed: Figure 4A As shown, a slurry droplet 10x is broken into each active material particle or each active material particle group as a unit to obtain a plurality of slurry droplets 10y. Figure 4B As shown, a first aggregated precursor 21x is broken into units of each active material particle or each group of active material particles to obtain a plurality of first precursors 21y. In other words, in the method disclosed herein, in addition to the fact that the granulation of the first precursor and the first particle is easily suppressed due to the presence of the second precursor and the second particle, even in the case where the granulation of the first precursor and the first particle occurs, a part of the granulation can be broken by airflow drying. In this regard, in the method disclosed herein, a slurry with a low solid content concentration that is easy to granulate or aggregate can be used, which can easily increase the processing speed when manufacturing the coated active material (first particle). In this way, in step S2, the slurry droplets and the precursor are broken by airflow drying, thereby easily shortening the manufacturing time and easily manufacturing a coated active material (first particle) with higher performance.

[0103] In step S2, the above drying and crushing can be performed simultaneously or separately. In step S2, the first airflow drying in which the drying of the slurry droplets is dominant and the second airflow drying in which the crushing of the precursor is dominant can be performed. In addition, step S2 can be repeated.

[0104] In step S2, the temperature of the heating gas can be any temperature that allows the solvent to volatilize from the slurry droplets. For example, it can be above 100°C, above 110°C, above 120°C, above 130°C, above 140°C, above 150°C, above 160°C, above 170°C, above 180°C, above 190°C, above 200°C, above 210°C, above 220°C, above 230°C, above 240°C or above 250°C. According to the new insights of the inventors, when the heating gas is at a high temperature, for example, above 250°C, it is easy to produce more second precursors and second particles, and it is easy to further suppress the aggregation and granulation of the first precursor and the first particles. It is believed that whether the surface of the active material is covered with the coating liquid varies greatly depending on the surface energy of the coating liquid. By setting the temperature of the heating gas to a high temperature, the coating liquid also becomes a high temperature, and the surface energy of the coating liquid changes greatly, and the amount of the coating liquid that can be fixed on the surface of the active material may be reduced.

[0105] In step S2, the supply amount (flow rate) of the heating gas can be appropriately set in consideration of the size of the device used, the supply amount of the slurry droplets, etc. For example, the flow rate of the heating gas can be 0.10 m / s. 3 / min or more, 0.15m 3 / min or more, 0.20m 3 / min or more, 0.25m 3 / min or more, 0.30m 3 / min or more, 0.35m 3 / min or more, 0.40m 3 / min or more, 0.45m 3 / min or more, or 0.50m 3 / minute or more, and can be 5.00m 3 / min or less, 4.00m 3 / min or less, 3.00m 3 / min or less, 2.00m 3 / min or less, or 1.00m 3 / min or less.

[0106] In step S2, the supply speed (flow rate) of the heating gas can be appropriately set in consideration of the size of the device used, the supply amount of the slurry droplets, etc. For example, the flow rate of the heating gas can be 1 m / s or more or 5 m / s or less, and can be 50 m / s or less or 10 m / s or less in at least a portion of the system.

[0107] In step S2, the treatment time (drying time) using the heated gas can be appropriately set in consideration of the size of the device used, the amount of slurry droplets supplied, etc. For example, the treatment time can be 5 seconds or less or 1 second or less.

[0108] In step S2, a heating gas that is substantially inactive to the active material and the coating liquid may be used. For example, an oxygen-containing gas such as air, an inactive gas such as nitrogen or argon, dry air with a low dew point, etc. may be used. The dew point at this time may be below -10°C, below -50°C, or below -70°C.

[0109] As an apparatus for performing airflow drying, for example, a spray dryer can be used, but the invention is not limited thereto.

[0110] 1.2.2 First Precursor

[0111] The first precursor comprises an active material and a component from the coating liquid. Specifically, in the first precursor, at least a portion of the surface of the active material is coated with a component from the coating liquid. The details of the active material and the details of the components contained in the coating liquid are as described above. There is no particular limitation on the amount of the active material attached by the component from the coating liquid, and it can be appropriately adjusted according to the thickness of the target coating layer, etc.

[0112] 1.2.3 Second Precursor

[0113] The second precursor does not contain active substances, but contains components from the coating liquid. As described above, when the slurry droplets are dried by air flow, due to the "excess liquid", a part of the coating liquid is easily dried and condensed without being attached to the active substance. That is, it can be said that the second precursor is formed by condensing and drying the coating liquid and the active substance independently when the slurry droplets are dried by air flow. Since the second precursor does not contain active substances, it is easy to become smaller than the first precursor, and it is easy to become spherical as described later. In this way, in the method disclosed in the present invention, by producing the second precursor together with the first precursor, it is easy to suppress the granulation of the first precursor, and finally it is easy to obtain fine first particles (coated active substances).

[0114] 1.3 Process S3

[0115] like Figure 5 As shown, in step S3, the first precursor 21 and the second precursor 22 obtained in step S2 are fired. Thus, the first particles 31 and the second particles 32 are obtained. Figure 5 As shown, the first particle 31 has an active material 10a and a coating layer 10d that covers at least a portion of the surface of the active material 10a. That is, the first particle 31 is a coated active material. As described above, it can be said that the coating layer 10d of the first particle 31 contains a component from the coating liquid 10b. On the other hand, the second particle 32 does not contain the active material 10a but contains the same components as the components constituting the above-mentioned coating layer 10d. In other words, it can also be said that the second particle 32 contains a component from the coating liquid 10b.

[0116] 1.3.1 Firing conditions

[0117] In the calcination of the precursor, for example, a muffle furnace or a hot plate can be used. Alternatively, the calcination of the precursor can also be carried out in the above-mentioned airflow drying. That is, in step S2, the slurry droplets are airflow dried to become a precursor, and then the precursor is heated and maintained in the airflow, thereby the calcination of the precursor involved in step S3 can be carried out. There is no particular limitation on the calcination conditions (calcination temperature, calcination time, calcination atmosphere, etc.), and they can be appropriately set according to the type of first particles as the coated active material. The calcination temperature can be, for example, above 100°C, above 150°C, above 180°C, above 200°C, or above 230°C, and can be below 350°C, below 300°C, or below 250°C. The calcination temperature in step S3 can be higher than the temperature of the airflow drying in step S2, or lower than it, or the same as the temperature of the airflow drying. The firing time can be, for example, more than 1 hour, more than 2 hours, more than 3 hours, more than 4 hours, more than 5 hours, or more than 6 hours, and can be less than 20 hours, less than 15 hours, or less than 10 hours. The firing atmosphere can be, for example, an air atmosphere, a vacuum atmosphere, a dry air atmosphere, a nitrogen atmosphere, or an argon atmosphere.

[0118] 1.3.2 First particle (coated active material)

[0119] The first particle is obtained by calcining the first precursor. The details of the active material constituting the first particle are as described above. The first particle has a coating layer, which contains components from the coating liquid. There is no particular limitation on the thickness of the coating layer in the first particle, for example, it can be more than 0.1nm, more than 0.5nm or more than 1nm, and it can be less than 500nm, less than 300nm, less than 100nm, less than 50nm or less than 20nm. In addition, the coating layer can also cover more than 70% or more than 90% of the surface of the active material. It should be noted that the coverage of the coating layer on the surface of the active material can be calculated by observing a scanning electron microscope (SEM) image of a cross-section of the particle, or by calculating the element ratio of the surface using X-ray photoelectron spectroscopy (XPS).

[0120] The particle size (D90) of the first particles is not particularly limited, and may be, for example, 1 nm or more, 10 nm or more, 100 nm or more, 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, 6 μm or more, 7 μm or more, 8 μm or more, or 9 μm or more, and may be 50 μm or less, 30 μm or less, 20 μm or less, or 10 μm or less. It should be noted that the particle size D90 is the particle size at which the cumulative value of the volume-based particle size distribution determined by a laser diffraction / scattering method reaches 90%.

[0121] In the first particle, the coating layer may have a plurality of pores. The pores may be, for example, cavities, bubbles (voids) or gaps (gap), etc. There is no particular limitation on the shape of each pore. For example, the cross-sectional shape of each pore may be circular or elliptical. There is no particular limitation on the size of each pore. For example, when observing the cross section of the first particle, the circle equivalent diameter of the pore may be greater than 10 nm or less than 300 nm. There is no particular limitation on the number of pores in the coating layer. There is no particular limitation on the position of the pores in the coating layer, and there may be pores at the interface between the active material and the coating layer, or there may be pores in the coating layer. The coating layer may also have a plurality of pores enclosed in the inner side (active material side) relative to its outermost surface (the surface on the opposite side of the active material).

[0122] In the first particle, the coating layer has a plurality of pores, and the following effects can be expected. For example, the contact between the first particle and other battery materials becomes favorable, which may promote the movement of electrons and ions. In addition, the first particle exhibits buffering properties, and thus, the performance of electrodes and batteries may be improved. For example, when the active material expands during charging and discharging, or when pressure is applied to the coated active material during the pressing process of the electrode, it is believed that due to the above-mentioned buffering properties, the stress applied to the active material is reduced, and the rupture of the active material is suppressed.

[0123] As a method for forming a plurality of pores in the coating layer, for example, the following method can be cited. That is, in the above-mentioned method of the present disclosure, a spray dryer can be used to dropletize and airflow dry the slurry. In this case, by rapid drying as a characteristic of the spray dryer, the detachment of the components contained in the slurry (coating solution and active substance) and the generation of the film occur roughly at the same time. That is, it is believed that the shape of the film changes greatly due to the influence of the physical force received when the components are detached, and the film is solidified in a state where the influence remains, so that a plurality of pores are formed in the coating layer as described above. It is believed that even if the type of coating liquid contained in the slurry changes, this phenomenon will occur in the same way, especially when using a low-boiling point solvent such as water (a solvent that is accompanied by rapid gasification during the drying process), it is expected that this phenomenon will occur dominantly.

[0124] The first particles obtained after calcination in step S3 have a coating layer, etc., and therefore tend to be larger than the active material used in step S1. On the other hand, as described above, in the method of the present disclosure, due to the presence of the second precursor and the second particles, the granulation of the first precursor and the first particles is easily suppressed, so the particle size of the first particles is difficult to be excessively increased. For example, the particle size (D90) of the mixture of the first particles and the second particles obtained in step S3 may be 1.10 times or more of the particle size (D90) of the active material used in step S1, and may be 1.50 times or less, 1.40 times or less, or 1.30 times or less.

[0125] 1.3.3 Second Particle

[0126] The second particle is obtained by calcining the second precursor. The second particle is different from the first particle and does not contain an active material. In addition, the second particle contains the same components as the components contained in the coating layer of the first particle. In other words, the second particle contains components derived from the coating liquid. In the method disclosed in the present invention, due to the presence of the second precursor and the second particle, the granulation of the first precursor and the first particle is suppressed, and it is easy to obtain fine first particles as the coated active material. It is believed that the more the amount of the second precursor relative to the first precursor, and the more the amount of the second particle relative to the first particle, the more the granulation of the first precursor and the first particle is suppressed. As described above, the amount of the second precursor relative to the first precursor and the amount of the second particle relative to the first particle can be adjusted by changing the temperature (gas supply temperature) and the spray speed (liquid delivery speed) of the heating gas in step S2. That is, the higher the temperature of the heating gas, and the higher the spray speed, the easier it is to produce a large amount of second precursors and second particles. There is no particular limitation on the ratio of the first particle to the second particle. For example, based on the total of the first particles and the second particles (100% by volume), the second particles may account for more than 0.1% by volume or more than 1% by volume, and may account for less than 10% by volume or less than 5% by volume. It should be noted that the ratio of the first particles to the second particles may be calculated from an SEM image of an electrode mixture containing the first particles and the second particles.

[0127] The second particles do not contain active materials, so they are naturally smaller than the first particles. The particle size (D90) of the second particles is not particularly limited, and can be, for example, 1 nm or more, 10 nm or more, 100 nm or more, or 300 nm or more, and can be 10 μm or less, 8 μm or less, 5 μm or less, or 3 μm or less.

[0128] It can be said that the second particle is, for example, a particle obtained by further firing a second precursor obtained by volatilizing and condensing a solvent from a slurry droplet substantially free of solid components such as an active material. That is, at the stage of the slurry droplet, a spherical shape as a stable droplet shape is maintained, and the spherical droplet can be directly condensed into a second precursor and a second particle. In this regard, the shape of the second precursor and the second particle can also be spherical. Specifically, for example, the roundness (circularity) of the cross section of the second particle can be more than 0.30 or more than 0.35, or can be less than 1.00 or less than 0.85. The calculation formula for the roundness (circularity) of the cross section of the second particle will be described later.

[0129] 1.4 Specific examples of steps S1 to S3

[0130] The case of manufacturing a coated active material having a coating layer containing lithium niobate on the surface of the positive electrode active material is exemplified. For example, using particles containing lithium oxide as the positive electrode active material, using a solution (such as an aqueous solution) containing a peroxo complex of lithium ions and niobium as the coating liquid, the above steps S1 and S2 are performed to obtain a first precursor and a second precursor. In the first precursor, lithium and niobium from the coating liquid adhere to the surface of the positive electrode active material. In addition, the second precursor contains lithium and niobium from the coating liquid. By sintering the first precursor and the second precursor, a coated active material as a first particle and a second particle are obtained. Specifically, together with the first particle (coated active material) having a coating layer containing lithium niobate formed on the surface of the lithium oxide containing material as the positive electrode active material, a second particle containing lithium niobate is obtained.

[0131] 1.5 Other processes

[0132] By going through the above-mentioned steps S1 to S3, an electrode mixture containing at least the first particle and the second particle is obtained. The electrode mixture may contain other components in addition to the first particle and the second particle depending on its use. For example, in the case of obtaining an electrode mixture for a solid battery (a battery using a solid electrolyte), the method disclosed herein may include mixing at least the first particle, the second particle and the solid electrolyte, or may include mixing at least the first particle, the second particle, the solid electrolyte, a conductive additive and a binder. There is no particular limitation on the content of the first particle in the electrode mixture, for example, it may be 40% by mass or more and 99% by mass or less. In addition, there is no particular limitation on the content of the second particle in the electrode mixture, for example, it may be 1.0% by mass or less, 0.5% by mass or less or 0.1% by mass or less. The first particle and the second particle may be mixed with other components in a dry manner, or may be mixed in a wet manner using an organic solvent (preferably a non-polar solvent).

[0133] 1.5.1 Solid Electrolyte

[0134] The solid electrolyte can use a known substance. For example, an oxide solid electrolyte containing Li oxide of a perovskite type, NASICON type or garnet type, or a sulfide solid electrolyte containing Li and S as constituent elements can be used. In particular, when a sulfide solid electrolyte is used, a higher effect based on the technology disclosed in the present invention can be expected. As a specific example of a sulfide solid electrolyte, LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, Li3PS4, Li2S-P2S5-GeS2, etc. can be listed, but it is not limited to these. The solid electrolyte can be amorphous or crystalline. The solid electrolyte can be used alone or in combination of two or more.

[0135] 1.5.2 Conductive additives

[0136] Specific examples of conductive aids include carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), Ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF), or metal materials that can withstand the environment in which the battery is used, but are not limited to these. The conductive aid may be used alone or in combination of two or more.

[0137] 1.5.3 Adhesives

[0138] As specific examples of adhesives, acrylonitrile butadiene rubber (ABR) adhesives, butadiene rubber (BR) adhesives, polyvinylidene fluoride (PVdF) adhesives, styrene butadiene rubber (SBR) adhesives, polytetrafluoroethylene (PTFE) adhesives, polyimide (PI) adhesives, etc. can be listed, but are not limited to these. The adhesive can be used alone or in combination of two or more.

[0139] 2. Electrode manufacturing method

[0140] The electrode mixture produced by the method disclosed herein can be used as a material for forming electrodes of various batteries. In this regard, the technology disclosed herein also has an aspect of a method for producing an electrode. For example, the method for producing an electrode disclosed herein may include: obtaining an electrode mixture by the method disclosed herein, and molding the electrode mixture to obtain an electrode having a layer containing the electrode mixture (molding process).

[0141] In the forming process, the electrode mixture can be formed by dry forming or wet forming. In addition, the electrode mixture can be formed alone or together with a current collector. Furthermore, the electrode mixture can also be integrally formed on the surface of the electrolyte layer. As an example of a forming process, the following methods can be listed: a slurry containing an electrode mixture is applied to the surface of a current collector, and then a process of drying and optionally pressing is performed to make an electrode; or a powdered electrode mixture is put into a mold, etc., and formed by dry pressing to make an electrode. An example of the composition of an electrode will be described later.

[0142] 3. Manufacturing method of lithium-ion battery

[0143] The technology disclosed herein also has an aspect as a method for manufacturing a lithium ion battery. That is, the method for manufacturing a lithium ion battery disclosed herein may include: obtaining an electrode using the method for manufacturing an electrode disclosed herein, and obtaining a laminate including the electrode and an electrolyte layer.

[0144] When manufacturing a solid battery as a lithium ion battery, the electrolyte layer can be, for example, a layer comprising a solid electrolyte and a binder. The types of solid electrolytes and binders are as described above. Alternatively, when manufacturing an electrolyte battery as a lithium ion battery, the electrolyte layer can be, for example, a layer having a separator and an electrolyte. As for the separator and the electrolyte, it is sufficient to use known substances. The lithium ion battery can be manufactured through self-evident processes such as stacking of electrodes and electrolyte layers, connection of terminals to electrodes, storage in a battery case, and restraint of the battery. An example of the structure of a lithium ion battery will be described later.

[0145] 4. Electrode mixture

[0146] The technology disclosed in the present invention also has an aspect as an electrode mixture itself. That is, the electrode mixture disclosed in the present invention includes at least a first particle and a second particle, the first particle having an active material and a coating layer covering at least a portion of the surface of the active material, and the second particle does not contain the active material but contains the same components as the components constituting the coating layer. The first particle, the second particle and other components contained in the electrode mixture are as described above. For example, in the electrode mixture disclosed in the present invention, the roundness of the cross section of the second particle can be greater than 0.30 or greater than 0.35, and can be less than 1.00 or less than 0.85. In addition, as described above, in the electrode mixture disclosed in the present invention, the coating layer can contain at least lithium and niobium as constituent elements. Furthermore, as described above, the electrode mixture disclosed in the present invention can include at least the first particle, the second particle and a solid electrolyte.

[0147] 5. Electrodes

[0148] The technology disclosed in the present invention also has an aspect as an electrode itself. That is, the electrode disclosed in the present invention has a layer (electrode mixture layer) containing the above-mentioned electrode mixture. Figure 6 As shown, the electrode 50 according to one embodiment may include a current collector 52 in contact with the electrode mixture layer 51 in addition to the electrode mixture layer 51. The electrode may be used as a positive electrode or a negative electrode, and in particular, when used as a positive electrode (particularly as a positive electrode for a lithium ion battery), a higher effect of the technology disclosed in the present invention can be expected.

[0149] 5.1 Electrode mixture layer

[0150] As described above, the electrode mixture is formed to obtain an electrode mixture layer. The shape of the electrode mixture layer is not particularly limited, as long as it is appropriately determined according to the shape of the electrode. For example, the electrode mixture layer can be a roughly flat sheet, and its thickness can be, for example, more than 1 μm, more than 10 μm, or more than 30 μm, and can be less than 1 mm, less than 500 μm, or less than 100 μm.

[0151] In the electrode disclosed herein, when observing the cross section of the electrode mixture layer, the proportion of the second particles in the electrode mixture layer can be 0.02 area % or more or 0.03 area % or more. Thus, the granulation and aggregation of the first particles are more easily suppressed, and the performance of the electrode is likely to be further improved. There is no particular upper limit on the proportion of the second particles in the electrode mixture layer, for example, it can be 3.00 area % or less, 2.00 area % or less, or 1.00 area % or less.

[0152] It should be noted that the shape and size of the second particles contained in the electrode mixture layer can be quantified by performing image analysis after obtaining an SEM image of the electrode cross section (for example, the total number of pixels = 1024×700). Specifically, the SEM image of the electrode cross section is compared with the EDX mapping image to extract the second particles contained in the cross section. The elements that are the objects of EDX mapping can be appropriately selected according to the elements contained in the active material and the elements contained in the coating layer. It should be noted that in order to remove fine noise, pixels below the specified pixel (for example, less than 50 pixels) can also be excluded from the extraction object. The number of particles, the average particle size, the area occupied by the second particles, and the roundness (roundness) of the extracted second particles are calculated. In terms of the average particle size, each particle is approximated as a circle, and the diameter of the circle (area equivalent circle diameter) is used as the particle size to calculate the average value. In the electrode mixture layer, the number of pixels of each particle is calculated, and the area occupied by the second particles is calculated by the following formula (I). In addition, each particle was approximated by an ellipse, and the roundness (circularity) of the second particle was determined by the following formula (II).

[0153] (Area occupied by the second particles = (Number of pixels of each particle contained in the electrode mixture layer in the SEM image) / (Total number of pixels of the electrode mixture layer in the SEM image) ... (I)

[0154] (roundness = [4 × (particle area)] / [π × (major axis length) 2 ]… (II)

[0155] 5.2 Current Collector

[0156] The collector can adopt a common collector as the collector of the battery. The collector can be in the form of foil, plate, mesh, punched metal, foam, etc. The collector can be a metal foil or a metal mesh, or it can also be a carbon sheet. In particular, the metal foil has excellent handleability. The collector can be composed of multiple foils and sheets. As metals constituting the collector, Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, etc. can be listed. For the purpose of adjusting resistance, etc., the collector can have a coating on its surface. In addition, the collector can be a collector on which the above metal is plated or vapor-deposited on a metal foil or a substrate. In addition, when the collector is formed by multiple metal foils, there can be a layer between the multiple metal foils. There is no particular limitation on the thickness of the collector. For example, it can be more than 0.1μm or more than 1μm, or it can be less than 1mm or less than 100μm.

[0157] 6. Lithium-ion battery

[0158] The technology disclosed in the present invention also has an aspect as a lithium ion battery itself. Specifically, the lithium ion battery disclosed in the present invention has the above-mentioned electrode. The lithium ion battery can have an obvious structure as a battery together with the above-mentioned electrode. For example, Figure 7 As shown, the lithium ion battery 100 may include a positive electrode 50a, a negative electrode 50b, and the above-mentioned electrolyte layer 60. In the lithium ion battery of the present disclosure, at least one of the positive electrode 50a and the negative electrode 50b only needs to be the electrode 50 of the present disclosure. In particular, in the lithium ion battery, when the electrode 50 of the present disclosure is included as the positive electrode 50a, a higher effect of the technology of the present disclosure can be expected. The electrolyte layer is as described above.

[0159] Example

[0160] Hereinafter, the technology of the present disclosure will be further described with reference to examples, but the technology of the present disclosure is not limited to the following examples.

[0161] 1. Examples 1 to 8

[0162] 1.1 Preparation of Nb-containing coating solution

[0163] 987.4 g of ion exchange water and 44.2 g of niobic acid (Nb2O5·3H2O (Nb2O5 water content 72%)) were added to a container containing 870.4 g of 30% by mass hydrogen peroxide. Next, 87.9 g of 28% by mass ammonia water was added to the container. After the addition of the ammonia water, the contents in the container were stirred thoroughly to obtain a transparent solution. Furthermore, 10.1 g of lithium hydroxide·monohydrate (LiOH·H2O) was added to the obtained transparent solution to obtain a complex solution containing a peroxo complex of niobium and lithium ions as a coating solution.

[0164] 1.2 Preparation of slurry containing active substance and coating liquid

[0165] LiNi as active material 1 / 3 Mn 1 / 3 Co 1 / 3 20 g of O2 (manufactured by Nichia Chemical Industries, Ltd.) was placed in a mixer container and added to the coating solution prepared as described above to a predetermined solid content concentration, and stirred with a magnetic stirrer. The solid content concentrations in the coating solutions of the active materials of each example are shown in Table 1 below.

[0166] 1.3 Preparation of precursor

[0167] The slurry of each example prepared above was supplied to a spray dryer (Buch Company, small spray dryer B-290) at a predetermined liquid delivery rate using a liquid delivery pump, and the slurry was dropletized (step S1) and the slurry droplets were dried by air flow (step S2) to obtain a first precursor and a second precursor. The air supply temperature, air supply volume, and liquid delivery rate of the spray dryer are as shown in Table 1.

[0168] In each embodiment, the time required for conveying (feeding liquid) the slurry to the nozzle and performing dropletization in the spray dryer (dropletization processing time of step S1) and the time for airflow drying (airflow drying processing time of step S2) are both short times of less than 1 minute. It should be noted that the airflow drying processing time refers to the time from the end of supplying the slurry to the spray nozzle to the end of airflow drying.

[0169] 1.4 Firing of Precursor

[0170] The first precursor and the second precursor were fired at 200° C. for 5 hours using a muffle furnace to synthesize lithium niobate on the surface of the active material in the first precursor, thereby obtaining first particles as the coated active material. In addition, the second precursor was fired at the same time to obtain second particles containing lithium niobate.

[0171] 2. Example 9

[0172] The slurry preparation, precursor preparation and precursor firing were carried out in the same manner as in Example 8 except that a P-containing coating liquid was used instead of the Nb-containing coating liquid.

[0173] The phosphorus-containing coating liquid was adjusted as follows. That is, 866.6 g of ion-exchanged water was added to a container containing 59.8 g of phosphoric acid having a concentration of 85% by mass, and the mixture was stirred sufficiently to obtain a transparent solution. 70.2 g of lithium hydroxide monohydrate (LiOH·H2O) was added to the obtained transparent solution to obtain an aqueous solution containing phosphoric acid ions and lithium ions as a coating liquid.

[0174] 3. Comparative Examples 1 and 2

[0175] The coated active material was obtained using a tumbling flow granulation coating apparatus under the following conditions.

[0176] 3.1 Comparative Example 1

[0177] like Figure 8 As shown in the figure, a tumbling flow granulation coating apparatus "MP-01" (manufactured by Pawleck Co., Ltd.) was used to coat LiNi as an active material. 1 / 3 Mn 1 / 3 Co 1 / 3 1 kg of O2 (manufactured by Nichia Chemical Industry Co., Ltd.) was sprayed with 2000 g of the Nb-containing coating liquid prepared above, and dried to obtain a precursor of a coated active material (S11). The obtained precursor was calcined under the same conditions as in the above example (S12) to obtain the coated active material involved in Comparative Example 1.

[0178] In addition, the operating conditions of the tumble flow granulation coating device are as follows.

[0179] Atmosphere gas: dry air with dew point below -65℃

[0180] Air supply temperature: 200℃

[0181] Air supply volume: 0.45m 3 / minute

[0182] Rotor speed: 400rpm

[0183] Spray speed: 4.4g / min

[0184] 3.2 Comparative Example 2

[0185] A coated active material was obtained in the same manner as in Comparative Example 1 except that the P-containing coating liquid was used instead of the Nb-containing coating liquid.

[0186] 4. Evaluation conditions

[0187] 4.1 Particle size and particle size distribution determination

[0188] In each embodiment and comparative example, for the positive electrode active material before coating, a laser diffraction scattering measuring device (Aerotrac II manufactured by Microtrac BEL) was used to measure the particle size (D10, D50, D90 and D99) at the cumulative values ​​of 10%, 50%, 90% and 99% in the volume-based particle size distribution. In addition, in each embodiment and comparative example, the particle size (D10, D50, D90 and D99) was similarly measured for the particles (first particles and second particles) obtained after sintering. For each of the particle sizes D10, D50, D90 and D99, the ratio of the particle size of the first particle and the second particle after sintering to the particle size of the positive electrode active material before coating (particle size after sintering / particle size before coating) was calculated, and the results are shown in Table 1 below.

[0189] 4.2 Evaluation of electrodes and batteries

[0190] 4.2.1 Preparation of positive electrode

[0191] The sintered particles in each embodiment and comparative example are weighed with the sulfide solid electrolyte (10LiI-15LiBr-37.5Li3PS4) in a volume ratio of 6:4, and they are put into heptane together with 3% by mass of vapor-grown carbon fiber (VGCF) (produced by Showa Denko) as a conductive aid and 0.7% by mass of butadiene rubber (produced by JSR) as a binder. Then, they are mixed to prepare a positive electrode mixture. After the prepared positive electrode mixture is fully dispersed with an ultrasonic homogenizer, it is applied on aluminum foil and dried at 100°C for 30 minutes. Then, it is punched into 1 cm 2 The size of was obtained to obtain the positive electrode involved in each embodiment and comparative example.

[0192] The cross section of the obtained positive electrode was observed, and the area ratio of the second particles in the positive electrode mixture layer was measured. The area ratio of the second particles was measured by image analysis using the above-mentioned SEM image and EDX mapping image. The results are shown in Table 1 below.

[0193] 4.2.2 Preparation of negative electrode

[0194] The negative electrode active material (layered carbon) and the sulfide solid electrolyte (10LiI-15LiBr-37.5Li3PS4) were prepared in a volume ratio of 6:4, and they were put into heptane together with 1.2% by mass of butadiene rubber (manufactured by JSR Corporation) as a binder. Then, the negative electrode mixture was prepared by mixing them. After the prepared negative electrode mixture was fully dispersed with an ultrasonic homogenizer, it was applied on a copper foil and dried at 100°C for 30 minutes. Then, it was punched into 1 cm 2 of size, thus obtaining the negative electrode.

[0195] 4.2.3 Fabrication of solid electrolyte layer

[0196] Inward cross-sectional area 1cm 2 64.8 mg of sulfide solid electrolyte (10LiI-15LiBr-37.5Li3PS4) was added to the cylindrical ceramic, smoothed, and pressed at 1 ton to form a solid electrolyte layer.

[0197] 4.2.4 Battery Production

[0198] The positive electrode prepared above was stacked on one surface of the solid electrolyte layer, and the negative electrode prepared above was stacked on the other surface, and pressed at 4.3 tons for 1 minute. Then, stainless steel bars were placed between the two electrodes and restrained at 1 ton to obtain the lithium ion batteries involved in each embodiment and comparative example.

[0199] 4.2.5 Resistance measurement

[0200] The 5s resistance of the lithium ion battery obtained as described above was measured at SOC 40%. It should be noted that the resistance of the batteries involved in Examples 1 to 8 was evaluated relative to the resistance of the battery involved in Comparative Example 1 as a reference (100), and the resistance of the battery involved in Example 9 was evaluated relative to the resistance of the battery involved in Comparative Example 2 as a reference (100).

[0201] 4.2.6 Output measurement

[0202] For the lithium-ion batteries of each embodiment and comparative example, after adjusting the open circuit voltage (OCV) to 3.66V, constant power discharge was performed, and the maximum power value that could be discharged within 5 seconds was measured as the battery output. It should be noted that the cut-off voltage was 2.5V. Regarding the output of the batteries involved in Examples 1 to 8, the output of the battery involved in Comparative Example 1 was used as a reference (100) for relative evaluation. In addition, regarding the output of the battery involved in Example 9, the output of the battery involved in Comparative Example 2 was used as a reference (100) for relative evaluation.

[0203] 5. Evaluation results

[0204] The evaluation results are shown in the following Table 1. It should be noted that in Table 1, "total treatment time" refers to the sum of "slurry droplet treatment time (spraying time)" and "airflow drying treatment time" in the examples, and in the comparative examples, it is the total time of the treatment of drying while spraying the coating liquid on the active material. "Total treatment speed" refers to the value obtained by dividing the amount of active material used by the total treatment time.

[0205] [Table 1]

[0206]

[0207] In tumble flow coating, if the spray speed of the coating liquid is fast, granules are produced by liquid cross-linking. In addition, in tumble flow coating, the effect of breaking up the particles during drying is weak, and once granules are produced, it is difficult to crush them. Therefore, in tumble flow coating, in order to avoid the granulation of particles, the spray speed must be slowed down. In the past, for example, as in the comparative example, 2000g of coating liquid was delivered at 4.4g / min, and the liquid delivery time reached 444 minutes. In contrast, according to the embodiment, it can be seen that compared with the comparative example, the coated active material can be manufactured in a short time. In the embodiment, by the presence of the second precursor and the second particle together with the first precursor and the first particle, the aggregation and granulation of the first precursor and the first particle can be suppressed. In addition, even in the case of granules of the first precursor, the granules can be broken by airflow drying. Therefore, a slurry with a low solid content concentration can be used, and the processing speed can be easily increased. That is, compared with the conditions shown in Table 1, it can be processed at a high speed.

[0208] In addition, it can be seen that the resistance and output of the lithium-ion battery using the first particles and the second particles manufactured in the examples are the same as or superior to the resistance and output of the lithium-ion battery using the coated active material manufactured in the comparative example. In particular, it can be seen that when the gas supply temperature (heating gas temperature) is a high temperature of 250°C or more (Examples 6 to 8), among which, when the gas supply temperature is a high temperature of 250°C or more and the liquid feeding rate is a high speed of 1.0 g / sec or more (Examples 7 and 8), a large amount of second particles are generated and the granulation of the first particles is suppressed. As a result, the resistance of the lithium-ion battery is significantly reduced and the output is significantly improved. It is believed that by suppressing the granulation of the first particles, the battery reaction can be carried out more efficiently using the active material, thereby reducing the resistance of the electrode and the battery.

[0209] In addition, according to the results of Examples 1 to 9 and Comparative Examples 1 and 2, it can be seen that according to the technology disclosed in the present invention, the desired effect is exerted regardless of the type of coating liquid. However, the inventors have found that when using a coating liquid containing P, even if the active materials are excessively granulated with each other during tumbling flow coating, it is difficult to properly coat the surface of the active material by setting the spray speed to a low speed as described above. In addition, the coating layer formed by the coating liquid containing P has an initial resistance higher than that formed by the coating liquid containing Nb, and as a result, the output of the battery becomes smaller. That is, within the range confirmed in this embodiment, Examples 1 to 8 have low resistance and high output compared to Example 9.

[0210] It should be noted that, from the results of Examples 1 to 3, even if the solid content concentration of the slurry is changed, no significant difference is observed in the granulation inhibition effect of the active substance. In addition, from the results of Examples 1 and 4, even if the air supply volume during spray drying is changed, no significant difference is observed in the granulation inhibition effect of the active substance. On the other hand, when comparing Examples 1 to 8 as a whole, the higher the air supply temperature (temperature of the heating gas), the higher the air supply temperature and the faster the liquid delivery speed, the higher the granulation inhibition effect of the active substance tends to be. It can be considered that whether the surface of the active substance is coated varies greatly depending on the surface energy of the coating liquid. It is considered that since the surface energy of the coating liquid is strongly affected by temperature, the sensitivity of the air supply temperature becomes greater.

[0211] In addition, in Table 1, it is believed that the reason why the particle size ratio for particle size D10 is lower than 1.00 (smaller after calcination than before coating) is that the aggregation of active materials before coating is eliminated by tumbling flow and spray drying. That is, it is believed that the aggregation of active materials before coating is weak in binding force between active materials compared with the case of granulation via the coating liquid, and can be easily broken. It should be noted that the presence of the second particles in the embodiment is considered to be very small and has almost no effect on the particle size D10. On the other hand, with respect to particle sizes D50 to D99, the particle size after calcination becomes larger than before coating. This is believed to be due to the effect of the enlargement of active material particles due to the coating of the coating liquid and the effect of granulation of the active material via the coating liquid. As shown in Table 1, it can be seen that according to the method involved in the embodiment, compared with the method involved in the comparative example, the manufacturing process can be accelerated, and granulation can be suppressed to the same extent as the method involved in the comparative example.

Claims

1. A method for producing an electrode mixture, comprising: Dropping a slurry containing an active substance and a coating liquid to obtain slurry droplets; Allowing the slurry droplets to be airflow dried in a heated gas to obtain a first precursor and a second precursor; as well as The first precursor and the second precursor are fired to obtain first particles and second particles, wherein: The first precursor comprises the active material and a component from the coating liquid, The second precursor does not contain the active substance and contains components from the coating liquid. The first particle has the active material and a coating layer that covers at least a portion of the surface of the active material. The second particles do not contain the active material, and contain the same components as those constituting the coating layer.

2. The method according to claim 1, wherein: The temperature of the heating gas is 250° C. or higher.

3. The method according to claim 1 or 2, wherein: The slurry droplets are obtained by spraying the slurry.

4. The method according to claim 1 or 2, wherein: The coating solution contains at least a lithium source and a niobium source.

5. The method according to claim 4, wherein: The coating solution contains a peroxo complex of niobium as the niobium source.

6. The method according to claim 1 or 2, wherein: The method includes mixing at least the first particles, the second particles, and a solid electrolyte.

7. An electrode mixture obtained by the method for producing an electrode mixture according to claim 1, comprising at least first particles and second particles, wherein: The first particle has an active material and a coating layer that covers at least a portion of a surface of the active material. The second particles do not contain the active material, and contain the same components as those constituting the coating layer.

8. The electrode mixture according to claim 7, wherein The second particles have a cross-sectional circularity of 0.30 or more and 1.00 or less.

9. The electrode mixture according to claim 7 or 8, wherein The coating layer contains at least lithium and niobium as constituent elements. 10 . The electrode mixture according to claim 7 , comprising at least the first particles, the second particles, and a solid electrolyte.

11. An electrode comprising a layer comprising the electrode mixture according to any one of claims 7 to 10.

12. The electrode according to claim 11, wherein When observing a cross section of the layer, a ratio of the second particles in the layer is 0.02 area % or more.

13. A lithium ion battery comprising the electrode according to claim 11 or 12.

Citation Information

Patent Citations

  • Manufacture of semiconductor device

    JP1987069645A

  • Positive electrode active material for lithium ion secondary battery and manufacturing method thereof, positive electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2020009756A